1976
DOI: 10.1002/cpt1976192153
|View full text |Cite
|
Sign up to set email alerts
|

Human serum and myocardium digoxin

Abstract: Linear correlation was demonstrated between serum digoxin and papillary muscle digoxin concentrations in patients undergoing mitral valve surgery. The mean ratio of myocardial tissue to serum digoxin concentrations was 6711. This result supports the use of serum digoxin as a guide for assessing the degree of digitalization under steady-state conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…In fact, no simple relation seemed to exist between serum and myocardial concentrations of digoxin. This agrees with findings in some studies in adults and infants (Coltart et aI., 1972;Weintraub and Lasagna, 1973;Kim et aI., 1975), but is in conflict with others (Karjalainen et al, 1974;Gorodischer et al, 1976a;Hartel et al, 1976). The reasons for this discrepancy in result are unclear, but differences in experimental and methodological approaches may be of importance.…”
Section: 2 Distributionsupporting
confidence: 91%
“…In fact, no simple relation seemed to exist between serum and myocardial concentrations of digoxin. This agrees with findings in some studies in adults and infants (Coltart et aI., 1972;Weintraub and Lasagna, 1973;Kim et aI., 1975), but is in conflict with others (Karjalainen et al, 1974;Gorodischer et al, 1976a;Hartel et al, 1976). The reasons for this discrepancy in result are unclear, but differences in experimental and methodological approaches may be of importance.…”
Section: 2 Distributionsupporting
confidence: 91%
“…In patients with normal renal function digoxin concentrations were even higher in the kidney than in the myocardium, though with those in renal failure this did not occur. However, in myocardial samples devoid of fibrous tissue, Hartel et al (1976) have shown a linear correlation between serum digoxin and papillary muscle digoxin concentrations from 12 adults undergoing mitral valve replacement, confirming an earlier similar finding by Gillner et al (1974). Kim et al (1975) obtained tissue from 7 prema-ture infants, 4 full-term newborn infants, and 4 older children who had received digoxin for cardiac failure.…”
supporting
confidence: 84%
“…The majority of these have suggested that myocardial digoxin concentration is approximately 70 times higher than plasma concentration at steadystate (Carroll et al 1973;Carruthers et al 1975;Hartel et al 1976), although atrial drug concentrations may be somewhat lower than ventricular. A possible technical problem is raised by the use of conventional, direct radioimmunoassays which also detect digoxin metabolites.…”
Section: Uptake Of Digoxinmentioning
confidence: 96%
“…Direct myocardial biopsy is available under only very limited circumstances, such as in association with open heart surgery (Hartel et al 1976). The use of indirect methods is therefore essential in most circumstances, and radionuclide or nuclear magnetic resonance imaging might therefore be regarded as potentially suitable methods for both short and long term studies.…”
Section: Perioperative Biopsy and Imaging Techniquesmentioning
confidence: 99%